2022
DOI: 10.1186/s12889-022-14826-x
|View full text |Cite
|
Sign up to set email alerts
|

La vida en la frontera: protocol for a prospective study exploring stress and health resiliencies among Mexican-origin individuals living in a US-Mexico border community

Abstract: Background Mexican-origin adults living near the U.S.-Mexico border experience unique and pervasive social and ecological stressors, including poverty, perceived discrimination, and environmental hazards, potentially contributing to the high burden of chronic disease. However, there is also evidence that residents in high-density Mexican-origin neighborhoods exhibit lower prevalence rates of disease and related mortality than those living in other areas. Understanding the factors that contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…That is, a low level of educational attainment affects health literacy and English proficiency in Mexican-origin people with diabetes, leading to distress and poorer diabetes self-care [ 37 ]. In addition to the impact of education and income, Mexican-origin individuals have the lowest rates of healthcare utilization among different groups in the US, primarily due to barriers that hinder access to care [ 38 ]. Therefore, promoting CHWs interventions is crucial as they facilitate education and communication regarding healthcare, enabling patients to better understand the healthcare system and receive the necessary support and services they require [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, a low level of educational attainment affects health literacy and English proficiency in Mexican-origin people with diabetes, leading to distress and poorer diabetes self-care [ 37 ]. In addition to the impact of education and income, Mexican-origin individuals have the lowest rates of healthcare utilization among different groups in the US, primarily due to barriers that hinder access to care [ 38 ]. Therefore, promoting CHWs interventions is crucial as they facilitate education and communication regarding healthcare, enabling patients to better understand the healthcare system and receive the necessary support and services they require [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In general, depression and anxiety are often not diagnosed or underdiagnosed among Latine adults with diabetes due to cultural and linguistic barriers between health professionals and patients [ 24 , 39 ]. Thus, emotional well-being is critical to diabetes control [ 38 , 44 ], and these findings point toward the need to screen for depression and anxiety specifically among Mexican-origin individuals with diabetes during regular office visits [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…As such, the study included a qualitative explanatory phase designed to elucidate the potential protective factors articulated by the SRM, followed by a longitudinal study of the identified factors and their relationship to health outcomes among a cohort of border residents. We developed the BRS within the context of the qualitative phase of the study (see Duenas et al 2022 for a detailed description of the study protocol) [26].…”
Section: Methodsmentioning
confidence: 99%
“…In the parent study, CSF community health workers recruit participants through door-to-door randomized community-based sampling in two U.S. border communities. Eligible individuals complete a longitudinal survey in the home setting with an interview-style approach [26]. With the exception of question six, the nine-item BRS follows a 4-point Likert scale from 1 to 4 (1 = Completely disagree, 2 = Disagree, 3 = Agree, 4 = Completely Agree).…”
Section: Pilot Surveymentioning
confidence: 99%